"Unredressed" Grievances under RTE: Navigating the State Labyrinth. Issue 1 (14th January 2015) - Bhattacharjee, Malini; Mysoor, Dolashree
Abstract : Despite the refrain that India's statutory rights suffer from weak enforcement, little academic attention has been paid toward the role of grievance redress mechanisms that are crucial to rights enforcement. This article undertakes a systematic policy analysis of the grievance redress system under the Right to Education (RTE) Act at the level of both design and performance by illustrating it through the Karnataka example. Our findings show that the redress procedures under RTE in Karnataka are perplexing and poorly designed and have not led to enforcement of the right. With faltering administrative accountability, many complainants find themselves with unresolved grievances leading to unenforced or improperly enforced rights. Significant changes in the law and a substantial redesign of institutions are vital for effectively enforcing the RTE.